(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
For this project, the question we have worked with since 2020 was: in what way has religion affected us - our own religious experiences or those of others - in our anthropological work? This question refers directly to our field work and to the type of anthropology that we elaborate later. Or, put another way, what do these experiences mean that we later put aside in our writings, and in what way did they re-mean our understanding of the anthropological exercise? Still a little further: how did they modify our subjectivity and what impact did it have on our ways of positioning ourselves in the world? However, beyond an exercise in autoethnography in which we situate ourselves with our identities in the field, an anthropology of the experience of religion as we finally call it, places us in a more complex task.